Primary extrasensal nasal-type natural killer/T-cell lymphoma of the sigmoid colon and ıleocecal junction: A case report - Gao, Chang; Liu, Jia-Long; Zhang, Meng-Na; Qiu, Pei-Shan; Zhao, Xi-Xian; Zhao, Qiu; Liu, Jing; Shi, Xian-Yan (Turkish Journal of Gastroenterology, 2020)
Cite this article as: Gao C, Liu JL, Zhang MN, et al. Primary extrasensal nasal-type natural killer/T-cell lymphoma of the sigmoid colon and ıleocecal junction: A case report. Turk J Gastroenterol 2020; 31(12): 955-6.